The Impact of Globalization on the International Political System - Budiana, Muhammad (Journal of Management, 2023)
This research aims to examine the impact of globalization on the international political system, focusing on state interdependence, national sovereignty, the role of non-state actors, and political stability. Globalization has been identified as a factor that affects international relations and political decision-making. This study uses a quantitative approach with multiple regression analysis method, where the Globalization Index, Economic Development Level, and their interaction are used as independent and moderator variables to assess their influence on the International Political System. The results showed that the Globalization Index and Economic Development Level had no significant effect on the international political system, with a significance value above 0.05. The hypothesis that globalization has a positive influence on state interdependence and reduces sovereignty in political decision-making is not supported by the data. Similarly, there is no evidence that globalization has a negative impact on political stability in countries that are highly dependent on the global economy.